Metabolic adaptation to acute metabolic stress via PFKFB3 upregulation in rodent beta cells - Chiba, Koki; Nomoto, Hiroshi; Izumihara, Rimi; Zhang, Xinxin; Kameda, Hiraku; Nakamura, Akinobu; Atsumi, Tatsuya (Frontiers in Endocrinology, 2025)
IntroductionPancreatic beta cells undergo metabolic remodeling in response to metabolic overload, but the functional significance of this remains unclear. 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) is a glycolytic regulator that may play a role in beta cell adaptation under acute metabolic stress. This study aimed to investigate the involvement of PFKFB3 in beta cell function under such stress.MethodsINS-1 832/13 cells and mouse-derived pancreatic islets were cultured under varying glucose concentrations. Male ob/+ and ob/ob mice were assigned to ad libitum feeding, restricted feeding, or sodium–glucose cotransporter 2 inhibitor (SGLT2i) treatment groups. Glucose tolerance, insulin secretion, and expression of metabolism-related genes were assessed. Knockdown of PFKFB3 and pharmacological inhibition of glycolysis were used to evaluate its functional role; MTT assays were conducted to assess cellular metabolic activity.ResultsExposure to high glucose concentrations and excessive metabolic demand resulted in the upregulation of PFKFB3 expression in vitro and in vivo. Interventions such as restricted feeding and SGLT2i administration partially reduced metabolic stress-associated PFKFB3 upregulation in ob/ob mice. Knockdown of PFKFB3 or pharmacological inhibition of glycolysis resulted in decreased insulin secretion and impaired glucose tolerance. MTT assay results showed a time-dependent reduction in metabolic activity following Pfkfb3 knockdown, suggesting compromised cell survival under acute metabolic stress.ConclusionPFKFB3 upregulation under acute metabolic stress may be an adaptive response that helps maintain beta cell function. Suppression of PFKFB3 activity compromises insulin secretion and glucose tolerance, highlighting the importance of this pathway in metabolic adaptation to transient stress.